Dynamic Changes in Adiponectin and Resistin Drive Remission of Cardiometabolic Risk Biomarkers in Individuals with Obesity Following Bariatric Surgery - Amanda Machado Fiorotti; Amanda Cristina Araújo Gomes; Amanda Motta Bortoli; Beatriz Bobbio de Brito; Karolini Zuqui Nunes; Fabiano Kenji Haraguchi; Andressa Bolsoni-Lopes (MDPI AG, 2024)
The remission of obesity-related diseases following bariatric surgery appears to result from the reorganization of metabolic and hormonal pathways involving adipokines. This study aimed to investigate the relationship between changes in body adiposity and serum adipokine levels, as well as the association between variations in adiponectin or resistin levels and cardiometabolic risk blood biomarkers before and after Roux-en-Y gastric bypass. A longitudinal and prospective study was conducted with bariatric surgery patients. Anthropometric, body composition and blood biochemical parameters were measured before and at 2 and 6 months post-surgery. The data were analyzed using ANOVA, Pearson or Spearman correlation, and simple linear regression with a significance level of p < 0.05. Among 36 mostly female patients aged 30 to 39 years, significant reductions in body weight (−26.8%), fat mass (−50%), waist circumference (−18%) and waist-to-height ratio (−22%) were observed post-surgery. Serum adiponectin levels increased (+107%), while resistin (−12.2%), TNF-α (−35%), and PAI-1 (−11.1%) decreased. Glucose, insulin, CRP, cholesterol, LDL-c, triglycerides, and vitamin D also decreased. Waist circumference variation showed a positive correlation with PAI-1 and TNF-α and a negative correlation with adiponectin. The total fat mass showed a positive correlation with PAI-1. Adiponectin variation correlated negatively with glucose, resistin, and CRP but positively with HDL-c. Resistin showed a positive correlation with insulin and CRP. In conclusion, 6 months post-bariatric surgery, reducing abdominal adiposity had a more significant impact on serum adipokine levels than total fat mass. Adiponectin increase and resistin decrease acted as endocrine mediators driving the remission of cardiometabolic risk biomarkers in individuals with obesity following Roux-en-Y gastric bypass.